Mechanical size effects in a single crystalline equiatomic FeCrCoMnNi high entropy alloy. (1st March 2017) - Raghavan, R.; Kirchlechner, C.; Jaya, B.N.; Feuerbacher, M.; Dehm, G.
Abstract: The size dependence of the mechanical behavior of a single crystalline equiatomic FeCrCoMnNi single phase high entropy alloy was studied using in situ SEM microcompression. Electron back-scattered diffraction was used in conjunction with high-resolution scanning electron microscopy to identify the dominant slip system activated for accommodating plastic flow. The scaling of the yield strength with the size of the micropillar is discussed in comparison with the size dependence observed in face-centered and body-centered cubic single crystalline metals. Graphical abstract: